HEALTH AND SAFETY FOR INFRASTRUCTURE PROJECTS: PPE ADAPTATION - ISMAIL MUBARAK, AHMAD SYAWAL IDDIL (Universiti Teknologi PETRONAS, 2020)
The construction industry is a dynamic and revolutionary industry that come up with projects in terms of infrastructure and buildings. This dynamic and revolutionary industry has been facing with safety challenges in every project. The statistic has shown that the increases in fatality cases and permanent disablement cases due to accidents at the Malaysia’s construction sites are one of the highest compares to other sectors, which become a severe issue, and serious consideration is needed to be taken. On top of that, the humanity is currently facing the COVID-19 pandemic challenge, a new situation that foresees the application of specific measures, including adjunctive personal protective equipment (i.e., facemasks and gloves) is needed to reduce the potential transmission of the COVID-19.